Aluminum-Magnesium Hydroxycarbonate/Azo Dye Hybrids as Novel Multifunctional Colorants for Elastomer Composites - Szadkowski, Bolesław (Polymers (Basel), 2018)
This study presents the preparation and characterization of new organic-inorganic pigments based on aluminum-magnesium hydroxycarbonate (LH) and azo dyes. Solvent resistance studies, XRD, SEM, and TGA confirmed the successful formation of hybrid pigments, which were characterized in terms of their physicochemical properties. The new hybrid pigments were applied in acrylonitrile-butadiene (NBR) and ethylene-propylene (EPM) rubber composites and cured with sulfur and peroxide curing systems, respectively. The mechanical properties, dispersion quality, and flame-retardant properties of the NBR/hybrid and EPM/hybrid pigment composites were determined by dynamic mechanical analysis (DMA), SEM, and microscale combustion calorimetry (MCC). Complex experimental investigations revealed that the layered nature of hybrid pigments could improve the barrier ability and flame retardancy of elastomer composites. In comparison to unmodified aluminum-magnesium hydroxycarbonate, the modified LH dye structures contributed to significantly decrease the heat release rate and the total heat release of the NBR and EPM composites, offering a new approach to imparting low flammability to elastomer materials.